Thyroid Hormones Play Role in Sarcopenia and Myopathies - Bloise, Flavia F.; Oliveira, Thamires S.; Cordeiro, Aline; Ortiga-Carvalho, Tania M. (Frontiers in Physiology, 2018)
Skeletal muscle maintains posture and enables movement by converting chemical energy into mechanical energy, further contributing to basal energy metabolism. Thyroid hormones (thyroxine, or T4, and triiodothyronine, or T3) participate in contractile function, metabolic processes, myogenesis and regeneration of skeletal muscle. T3 classically modulates gene expression after binding to thyroid hormone nuclear receptors. Thyroid hormone effects depend on nuclear receptor occupancy, which is directly related to intracellular T3 levels. Sarcolemmal thyroid hormone levels are regulated by their transport across the plasma membrane by specific transporters, as well as by the action of deiodinases types 2 and 3, which can activate or inactivate T4 and T3. Thyroid hormone level oscillations have been associated with the worsening of many myopathies such as myasthenia gravis, Duchenne muscular dystrophy (DMD) and rhabdomyolysis. During aging skeletal muscle show a decrease in mass and quality, known as sarcopenia. There is increasing evidence that thyroid hormones could have a role in the sarcopenic process. Therefore, in this review, we aim to discuss the main effects of thyroid hormones in skeletal muscular aging processes and myopathy-related pathologies.